Unintended pregnancy prevention in women using psychoactive substances: A systematic review. (August 2020) - Yermachenko, Anna; Massari, Véronique; Azria, Elie; Clergue-Duval, Virgile; Thurn, Marion; El-Khoury Lesueur, Fabienne; Jauffret-Roustide, Marie; Melchior, Maria
Highlights: 22 studies aimed to prevent unintended pregnancy in substance users were analyzed. Interventions focused on unintended pregnancy prevention showed some efficacy. On-site counseling and free contraceptives predicted better outcomes than information. The postpartum period may be a window of opportunity to change contraceptive behavior. Generalizability of findings to countries other than the US is uncertain. Abstract: This systematic review seeks to evaluate the efficacy of interventions aimed at preventing unintended pregnancies in women using psychoactive substances. Seven electronic databases (Medline, EMBASE, CINAHL, Web of Science Core Collection, PsycINFO, Cochrane CENTRAL database) were searched in October 2017. Twenty-two articles met our inclusion criteria. Interventions based on behavior change theory yielded an increase in the initiation of effective contraception as compared with provision of written information materials. The effect was more pronounced when the intervention provided on-site contraceptive counseling and free access to birth control. Financial incentives also seemed to effectively increase women's contraception intake. Case management interventions including pregnant and postpartum women with heavy levels of substance use showed promising results in terms of initiation of contraception, but rates of unintended pregnancy over long-term follow-up were nevertheless elevated. Finally, some interventions integrated family planning services into specialized centers taking care of pregnant and postpartum women with substance abuse. However, most studies aimed at postpartum and post-abortion contraception used a non-comparative design and had a number of methodological flaws. The risk of bias in most studies is high. All interventions with a primary or secondary focus on the prevention of unintended pregnancy in women using psychoactive substances short-term improvements in contraception intake, but it is unclear if these effects last or have any impact on unintended pregnancy rates in the long-term.